A bajulação das massas - Franz Josef Brüseke; Héctor Ricardo Leis (Ciências Sociais Unisinos)
All modern social philosophies capitulate to the problem of horizontality and verticality. Not even their own existence can be thematized, and when it happens it immediately provokes the most passionate reactions. Being in the middle of the mass has become the fundamental rule of the contemporary democratic societies. The verdict of horizontality does not work only for politicians, but also to the society theorists. When these theorists accept this new role, they become suppliers of the "politically correct" speech. To Peter Sloterdijk we can distinguish speeches that fl atter the mass from others that despise or even try to offend it. To the author, the cultural struggles in the modernity seem to be reduced to a dispute between offenders and fl atterers of the massifi ed society. Since the greek political philosophy passing through the theoretical work of Tocqueville, Le Bon, Nietzsche, Ortega y Gasset and Heidegger, to acquire a curious political actualization with Lenin, Stalin, Hitler and others, the fl attered mass presents itself in the Latin American populism.